2008
DOI: 10.1245/s10434-007-9755-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression Status of Folate Receptor α Is Significantly Correlated with Prognosis in Non-Small-Cell Lung Cancers

Abstract: Higher levels of FOLR1 appear to be associated with better prognoses for patients with lung adenocarcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
87
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 33 publications
7
87
1
Order By: Relevance
“…Interestingly, however, a study that evaluated 119 non-small cell lung cancers found high FRa expression to be correlated with a better survival. 12 Nonetheless, the association of FRa expression with outcome should promote further research efforts on the prognostic significance of this marker in larger more heterogeneous colorectal cancer populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, however, a study that evaluated 119 non-small cell lung cancers found high FRa expression to be correlated with a better survival. 12 Nonetheless, the association of FRa expression with outcome should promote further research efforts on the prognostic significance of this marker in larger more heterogeneous colorectal cancer populations.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Its expression in certain epithelial tumors such as ovarian, breast, endometrial and non-small cell lung carcinoma has been associated with tumor behavior. [9][10][11][12] Importantly, FRa expression is tumor specific, as it is significantly higher in tumor cells than in normal cells. 13 FRa also has a high affinity for folic acid; and the high affinity is maintained when folic acid is conjugated with other molecules.…”
mentioning
confidence: 99%
“…1,8,9 Examining only lung adenocarcinomas, one study found FOLR1 (the gene encoding FRA) expression level was higher in well-differentiated compared with poorly differentiated tumors. 10 However, this result has not been confirmed at the protein level by immunohistochemistry. In this study, we initially set out to confirm the FRA protein expression pattern in NSCLC using antibody clone 26B3 that had been previously reported.…”
mentioning
confidence: 84%
“…TM4SF4 and CRYM genes were reported as tumor markers in lung cancer (17)(18)(19). FOLR1 gene was reported to be overexpressed in lung adenocarcinoma (20,21) and has critical involvement in drug resistance (22). METTL4 gene is known to be related to invasiveness and survival in lung cancer (23), and GUCY1B3 gene was reported to be involved in osteoclast signaling pathway (24).…”
Section: Validation Of Bone-preferentially Expressed Genesmentioning
confidence: 99%